Module as an Alternative In Material Delivery in an Online Drawing Course - Kusuma, Renata (Universitas Ciputra, 2021)
Information Technology development has been a driving force to improve teaching materials more effectively and efficiently nowadays. Revolution in teaching must be done continuously without neglecting reading or listening habits as has been practiced. In addition, in the year 2020 the global Covid-19 pandemic happened which has forced the education institution to change the conventional way of learning. Having been implemented to avoid the crowd, online learning needs a new strategy in its implementation. In fact, the online teaching and learning system is not free from obstacles, especially in courses requiring fine motor skills like those in the Basic Drawing course. One of the solutions to tackle the problems is by designing modules to be used as course materials. Online medium developed nowadays utilizes module platform with instructions in pdf format and video materials. This paper describes how modules have been used to implement teaching and learning in one semester during online learning nowadays. Key words: online learning, module, drawing course